Functional Connectivity and Genetic Profile of a “Double-Cortex”-Like Malformation - Sprugnoli, Giulia; Vatti, Giampaolo; Rossi, Simone; Cerase, Alfonso; Renieri, Alessandra; Mencarelli, Maria A.; Zara, Federico; Rossi, Alessandro; Santarnecchi, Emiliano (Frontiers in Integrative Neuroscience, 2018)
Laminar heterotopia is a rare condition consisting in an extra layer of grey matter under properly migrated cortex; it configures an atypical presentation of Periventricular Nodular Heterotopia (PNH) or a Double Cortex (DC) syndrome. We conducted an original functional MRI analysis in a drug-resistant epilepsy patient with “double cortex”-like malformation to reveal her functional connectivity (FC) as well as a wide genetic analysis to identify possible genetic substrates. Heterotopias were segmented into region-of-interests (ROIs), whose voxel-wise FC was compared to that of (i) its normally migrated counterpart, (ii) its contralateral homologous and (iii) those of 30 age-matched healthy controls. Extensive genetic analysis was conducted to screen cortical malformations-associated genes. Compared to healthy controls, both laminar heterotopias and the overlying cortex showed significant reduction of FC with the contralateral hemisphere. Two heterozygous variants of uncertain clinical significance were found, involving autosomal recessive disease-causing genes, FAT4 and COL18A1. This first functional connectivity analysis of a unique case of double cortex-like malformation revealed a hemispheric connectivity segregation both in the laminar cortex as in the correctly migrated one, with a new pattern of genes’ mutations. Our study suggests the altered FC could have an electrophysiological and functional impact on large-scale brain networks, and the involvement of not yet identified genes in “double cortex”-like malformation with a possible role of rare variants in recessive genes as pathogenic cofactors.